Perlindungan Hukum bagi Pemegang Merek pada Pembangunan Ekonomi Kreatif di indonesia - Suci Lestari; Annalisa Y; Muhammad Syaifuddin (VERITAS, 2023)
The development of the creative economy in Indonesia has become a main focus in recent years. One important aspect is legal protection for brand holders. This legal protection is crucial because brands are valuable assets in the creative industry. The Indonesian government has taken steps to strengthen brand protection through stricter laws and regulations. This legal protection includes the exclusive right of the brand owner to control the use of its brand, prevent counterfeiting, and protect the brand's reputation. Strong legal protection for brand owners has a positive impact on the growth of the creative economy. This has an impact on creative industry players willingness to invest in their brands, increase consumer trust, and encourage innovation. In a global context, brand protection opens the door for business expansion into international markets. But challenges remain, including effective law enforcement and awareness of brand rights. Therefore, collaboration between government, industry, and brand holders is very important to ensure effective legal protection while advancing Indonesia's creative economy.